The transformation of the silvopastoral landscape of Montesinho Natural Park (1995 – 2021) - Seripieri, Vitor Henrique Mistro (2023)
In the grazing areas of the Montesinho Natural Park (PNM), the diet of small ruminants is shaped by the available landscape, through the daily routes chosen by the shepherd to feed his flock. Thus, in addition to grazing, sheep and goats benefit from a combination of agricultural by-products and spontaneous vegetation, such as stubble fields, chestnut and olive groves, leftovers and pruning, as well as forests and scrubland. Changes in land use inevitably lead to adaptations in pastoral routes. An analysis of the evolution of the landscape explains the changes in the various land uses that make up the landscape, whether natural, semi-natural or anthropic, and which have been determined by global changes, in particular climate change. This study updated PNM's Natural and Semi-Natural Vegetation Map (1995), an analogue cartography of great historical value that was transferred to digital format, requiring a refinement of its geometry and classification to ensure that the results were not affected by the different methodologies inherent in its creation. To achieve this, we chose to adapt the polygons of the original cartography to the currently available land structure geometry, namely the ISIP geographical database, and to update it based on images from 2021, complemented by field visits and visual interpretation of other images from different seasons and dates. The data were processed in a GIS environment, using the QGIS tool, which allowed the interpretation of the landscape transformation in the last 26 years, quantified by a transition matrix, and the trend for the next 26 years. From the results we can conclude that there has been a drastic decrease in the areas of extensive and intensive dry farming (-47%), while an increase perennial plantation (olive and chestnut groves) (+38%) has been observed, with some peculiarities. The other categories remained constant and are expected to continue to increase, albeit at a slower rate.